Improvement of the transformation system in Chinese cabbage (Brassica campestris ssp. chinensis Makino) - YU Xiao-lin; CAO Jia-shu; XU Li-kui; QI Wen-wen; WANG Xiao-jing (浙江大学学报. 农业与生命科学版)
The binary plasmid vector pBI35S-AMF was transferred into cv. Shanghaiqing of Chinese cabbage pak-choi (Brassica campestris ssp. Mokino chinensis var. communis Tsen et Lee) and cv. Youqing of flowering Chinese cabbage (B. campestris ssp. chinensis Makino var. parachinensis (Bailey) Tsen et Lee) by Agrobacterium-mediated method. The pivotal factors, which influenced the transformation frequency, were compared, and the parameters of transformation system were optimized. It was showed that selective medium containing 300 mg/L ampicillin, which inhibited growth of Agrobacterium, led to production of more KanR shoots; the time required for preculture and co-culture was three days and two days respectively; and the efficiency of inoculation with LBA4404/pBI35S-AMF was significantly higher than with EHA105/pBI35S-AMF. Molecular analysis to KanR seedlings showed that the frequency of Southern blotting was 82.2% and most of transformants were multi-copies integration. Moreover, the results indicated that the efficiency of transformation system was stable.